HISTORICAL TRUTH AND FICTIONAL INVENTION IN ROMAN IVANYCHUK’S NOVEL “ZHURAVLYNYI KRYK” - Mykhalkiv, Y. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article highlights the study of the fiction transformation peculiarities of historical reality based on the novel “Cry of the Crane” (“Zhuravlynyi Kryk”) by R. Ivanichuk. The emphasis is put on the creation of the main characters’ images. It is proved that the close interaction between scientific awareness and the author’s artistic representation of the events from the past contributes to the creation of the author’s conception.